Transitioning paths: exploring factors that influenced the career choices of clinical nurses turned community college faculty in rural Texas community colleges - Keller, Brad J. (My University, 2026)
The nationwide shortage of nursing faculty has limited the capacity of nursing programs to meet workforce demands, a challenge especially acute in rural community colleges. This qualitative study examined the factors that influenced clinical nurses to transition into faculty roles and the conditions that contributed to their retention in rural Texas community colleges. Guided by the Theory of Planned Behavior (Ajzen, 1991) and informed by Maslow’s Hierarchy of Needs (Maslow, 1943), the study employed semi‑structured interviews with nursing faculty members across five institutions. Findings revealed that while participants acknowledged lower salaries in academia, they prioritized belonging, esteem, and self‑actualization over financial considerations. Retention was sustained by collegiality, professional autonomy, and the fulfillment derived from mentoring students and contributing to the profession. Analysis suggested that faculty often prioritized higher-order needs, even when lower-order needs were only partially met. The study contributes to the scholarship on nursing education by illuminating the interplay of personal, professional, and institutional factors that shape faculty career decisions in rural contexts. Implications include the need for leaders and policymakers to design strategies that address not only compensation but also the broader human needs of faculty.
Keywords: Nursing faculty; Rural community college; Faculty retention